Α‐synuclein assemblies sequester neuronal α3‐Na+/K+‐ATPase and impair Na+ gradient. (31st August 2015) - Shrivastava, Amulya Nidhi; Redeker, Virginie; Fritz, Nicolas; Pieri, Laura; Almeida, Leandro G; Spolidoro, Maria; Liebmann, Thomas; Bousset, Luc; Renner, Marianne; Léna, Clément; Aperia, Anita; Melki, Ronald; et al.
Abstract Extracellular α‐synuclein (α‐syn) assemblies can be up‐taken by neurons; however, their interaction with the plasma membrane and proteins has not been studied specifically. Here we demonstrate that α‐syn assemblies form clusters within the plasma membrane of neurons. Using a proteomic‐based approach, we identify the α3‐subunit of Na+/K+‐ATPase (NKA) as a cell surface partner of α‐syn assemblies. The interaction strength depended on the state of α‐syn, fibrils being the strongest, oligomers weak, and monomers none. Mutations within the neuron‐specific α3‐subunit are linked to rapid‐onset dystonia Parkinsonism (RDP) and alternating hemiplegia of childhood (AHC). We show that freely diffusing α3‐NKA are trapped within α‐syn clusters resulting in α3‐NKA redistribution and formation of larger nanoclusters. This creates regions within the plasma membrane with reduced local densities of α3‐NKA, thereby decreasing the efficiency of Na+ extrusion following stimulus. Thus, interactions of α3‐NKA with extracellular α‐syn assemblies reduce its pumping activity as its mutations in RDP/AHC.